2018
DOI: 10.1016/j.molimm.2018.06.149
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C1q as serum biomarker to detect active tuberculosis

Abstract: Lubbers et al.C1q as Biomarker for Active TB Conclusions: In summary, C1q levels are elevated in patients with active TB compared to LTBI in four independent cohorts. Furthermore, C1q levels from patients with TB were also elevated compared to patients with sarcoidosis, leprosy and pneumonia. Additionally, also in NHP we observed increased C1q levels in animals with active progressive TB, both in serum and in broncho-alveolar lavage. Therefore, we propose that the addition of C1q to current biomarker panels ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…9 Further on analysing publicly available blood gene expression microarray data of TB patients in comparison with latent TB or other lung diseases complement gene C1QC transcripts were observed more than 2 fold higher in TB patients in 78% (7/9) of the studies. 16 C1QC encodes for Cchain polypeptide of serum complement subcomponent C1q, which associates with C1r and C1s to yield the first component of the classical complement system. C1q is composed of 18 polypeptide chains which include 6 A-chains, 6 B-chains, and 6 C-chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Further on analysing publicly available blood gene expression microarray data of TB patients in comparison with latent TB or other lung diseases complement gene C1QC transcripts were observed more than 2 fold higher in TB patients in 78% (7/9) of the studies. 16 C1QC encodes for Cchain polypeptide of serum complement subcomponent C1q, which associates with C1r and C1s to yield the first component of the classical complement system. C1q is composed of 18 polypeptide chains which include 6 A-chains, 6 B-chains, and 6 C-chains.…”
Section: Discussionmentioning
confidence: 99%
“…10 One of the major limitations of the present study was its limited sample size. Further, previously published data reported a rapid decrease in C1qm RNA expression levels following Anti-tubercular treatment (ATT).Cliff et al 8 reported a decrease in blood C1qC genes after 1 week treatment; Cai et al 10 reported a significant decrease in the expression of the C1qC genes at 3 months of ATT and decrease in C1qC protein in peripheral blood at 6 months; whereas Lubbers et al 16 reported a gradual decrease in protein level until 6 months. Thus, evaluating serum C1qC levels during ATT might have provided much better insight of the biomarker potential of C1qC in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously described serum C1q as a biomarker of active TB disease 18,19 . In patients with active TB we observed significantly higher levels of serum C1q compared to individuals with latent Mtb infection or individuals with non-mycobacterial pneumonia.…”
Section: Tuberculosis (Tb) Causes 16 Million Deaths Annually Early mentioning
confidence: 99%
“…O comportamento da proteína C1q do Sistema Complemento durante PTB e LTBI foi analisado em um estudo com amostras intercontinentais de regiões endêmicas e não endêmicas da TB, também envolvendo pacientes com hanseníase, sarcoidose e pneumonia -visto que se trata de um biomarcador inflamatório bastante generalista que requer maior validação. A partir de uma análise combinada envolvendo todos os pacientes TB, grupos controle, LTBI e os pacientes tratados com sucesso o trabalho pode constatar que há um aumento significativo da C1q na PTB (p< 0.001) (LUBBERS et al, 2018).…”
Section: Biomarcadores Para Diagnóstico Da Doençaunclassified
“…Ambas seriam proteínas com atividade no sistema complemento, levando a crer que os níveis reduzidos possam ser devido a atenuação das ativações constantes do complemento, sendo aliviado pela conclusão da fase ativa da inflamação (WANG et al, 2018). Proteínas do complemento são estudadas na literatura da tuberculose (CAI et al, 2014;LUBBERS et al, 2018;SENBAGAVALLI et al, 2011), a FCN2 em específico apresenta alguns estudos com determinados pontos conflitantes, especialmente em relação ao impacto de seus genótipos na infecção (CHALMERS et al, 2015;LUO et al, 2013;XU et al, 2015).…”
Section: Biomarcadores Para Monitoramento Da Terapia E Curaunclassified